Sistem Pendukung Keputusan Penilaian Kinerja Karyawan PT. Injep Inti Cemerlang Dengan Metode AHP dan TOPSIS - Achmad Baroqah Pohan; Sofian Wira Hadi; Suparni Suparni (Ultima Computing : Jurnal Sistem Komputer, 2019)
During this time the performance appraisal of PT. Injep Inti Cemerlang has not been implemented optimally, especially in assessing employee performance. So far, performance appraisal is only determined from the results of its work, there are no clear assessment criteria. For this reason, a decision support system is needed to help find the best alternative for the selection of employees. in this study a decision support system for employee performance appraisal will be developed based on Attitude, Responsibility, Attendance, Discipline and Cooperation. This study aims to design a decision support system for employee performance appraisal using data collection methods by observation, interviews and giving questionnaires to employees of PT. Injep Inti Cemerlang. The data collected is carried out the process of analyzing data and looking for weighting values ​​using the AHP method and for ranking using the TOPSIS method, where each criterion is in this case. assessment factors and alternatives in this case employees are compared with criteria that have been weighted through the process of calculating the ahp and topsis method starting from giving the weighting of criteria by calculating with Ms.Excel and calculating with Expert Choice software. The results have been obtained from weighting the next ranking by the TOPSIS method. thus providing a value output that results in a system that assesses employees. This decision support system helps assess the performance of each employee of PT. Injep Inti Cemerlang in determining the employee who has the best performance